Bidirectional boost converter for high‐power transmission between energy storage battery and DC microgrid. Issue 7 (1st April 2019) - Song, Weiwei; Chen, Yanfeng; Zhang, Yongjun; Wen, An; Wei, Chengzhi
Abstract : When the energy storage battery (ESB) is introduced into the DC microgrid, the DC microgrid can perform demand side management well. To achieve flexible charge and discharge controls of the ESB, the grid‐connected device of the ESB needs to have a bidirectional power transmission control function with constant power. Based on this, this Letter first designs circuit topology of bidirectional boost converter for high‐power transmission between the ESB and the DC microgrid. Secondly, the control system based on the staggered timing trigger mechanism is developed, and the working process of the converter in the forward and reverse transmission of power is analysed. Finally, the bidirectional boost converter and its control system are verified by real‐time digital simulator platform. Simulation results show that the proposed converter and its control system can realise stable high‐power bidirectional transmission between the ESB and the DC microgrid, and achieve accurate tracking of the power reference value.